2019
DOI: 10.1002/edm2.72
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of antihyperglycaemic agents in diabetic kidney disease

Abstract: Diabetic kidney disease (DKD) is the major contributor to the mortality and the financial burden of diabetes, accounting for approximately 50% of the cases of end‐stage renal disease (ESRD) in the developed world. Several studies have already demonstrated that achieving blood pressure targets in DKD with agents blocking the renin‐angiotensin system confer superior renoprotection when compared to other agents. However, the effects on renal outcomes of antihyperglycaemic agents in these patients have not been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 103 publications
1
2
0
Order By: Relevance
“…Herein, the effect of saxagliptin on body weight compared with vildagliptin and control was nonsignificant. In consistence with our findings, previous studies showed that DPP‐4 inhibitors are weight neutral 11,51‐53 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Herein, the effect of saxagliptin on body weight compared with vildagliptin and control was nonsignificant. In consistence with our findings, previous studies showed that DPP‐4 inhibitors are weight neutral 11,51‐53 …”
Section: Discussionsupporting
confidence: 92%
“…In consistence with our findings, previous studies showed that DPP-4 inhibitors are weight neutral. 11,[51][52][53] Comparing the findings of saxagliptin and vildagliptin in the current study regarding glycaemic changes, both drugs showed similar reductions in HbA 1c . This was in parallel with Li et al 54 who reported that there was no significant difference amongst saxagliptin, vildagliptin or sitagliptin regarding HbA 1c changes after 24 weeks of treatment in diabetic patients on the combination of metformin and other traditional antidiabetic agents.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation